The cavernous sinus meningiomas’ dilemma: Surgery or stereotactic radiosurgery? - Fariselli, Laura (Rep Pract Oncol Radiother, 2016)
Despite the advances in techniques and technologies, the management of cavernous sinus (CS) meningiomas still remains a challenge for both neurosurgeons and radiation oncologists. On the other hand, the improvement of the anatomical knowledge and the microsurgical techniques together with diffusion of radiosurgery are currently changing the treatment strategy, opening new perspectives to the patients which are suffering from such lesions. The authors reviewed here the literature data. A multidisciplinary treatment algorithm is also proposed.